Good wives : Little women, part II - Alcott, Louisa May, 1832-1888. (Harmondsworth : Puffin Books, 1978)
This story follows the little girls into adult hood. There are autobiographical elements in the book as Jo's struggles in her writing career and other events are depicted.
First published in 1869.
Keywords: Sisters -- Children's fiction; Children's stories